ANALISIS KINERJA MESIN PENGERING TIPE RAK (TRAY DRYER) BERBAHAN BAKAR GAS UNTUK PROSES PENGERINGAN CHIP PISANG - , ASCARYO DWI ANGGORO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Drying banana chip are generally carried out by method of direct sun drying. Direct sun drying has many disadvantages, such is dependent of the weather. The research is done to compare tray dryer with LPG and biogas fuels. In addition, it is intended to allow drying ingredients in alternative energy, such as biogas. This research also aims to determine characteristics of drying banana chip and to analyze of air temperature to change water content. Banana is blanched in hot water at temperature 80- 85oC in 10 minutes for can easily peeled and then sliced in 2 mm and 6 mm thickness. The first phase, carried out with the drying gas flow variations, among 0,21 kg/h, 0,19 kg/h, and 0,17 kg/h and variations of shelfs for drying with biogas fuel. Decrease in water content of the discharge and air temperature and changing of water content over time is used to determine the value of drying rate constant ( k), activation energy (Ea), and efficiency (Î·). The result showed that the bigger of the gas flow, the water content decrease fastly. High of gas flow high temperature drying is able to evaporate the water content to 4- 8% in 10 hours and 18- 24 hours if using biogas fuel, the materials placed on the bottom shelf, water content can decrease rapidly. Constant rate of drying for the relationship between decreased water content and time at a constant rate period LPG dryer range from 9,85- 15,26%/h, whereas biogas dryer ranged from 4,97- 6,16%/h and the falling rate period range between 0,49- 0,81/h for LPG dryer, 0,24- 0,37/h for biogas dryer. Activation energy at constant periode about 452,73- 4.956,49 J/mol, while the falling rate periode ranged between 263,83- 2.159,96 J/mol. The dryng efficiency value of LPG dryer range from 20,97 to 23,15% and 19- 20% for biogas dryer. While the heating efficiency value range from 30,62- 38,81% for LPG dryer and 24- 25% for biogas dryer.